Third-generation pure alumina and alumina matrix composites in total hip arthroplasty: What is the evidence?. Issue 1 (10th January 2018) - Hannouche, Didier; Zingg, Matthieu; Miozzari, Hermes; Nizard, Remy; Lübbeke, Anne
Abstract : Wear, corrosion and periprosthetic osteolysis are important causes of failure in joint arthroplasty, especially in young patients. Ceramic bearings, developed 40 years ago, are an increasingly popular choice in hip arthroplasty. New manufacturing procedures have increased the strength and reliability of ceramic materials and reduced the risk of complications. In recent decades, ceramics made of pure alumina have continuously improved, resulting in a surgical-grade material that fulfills clinical requirements. Despite the track record of safety and long-term results, third-generation pure alumina ceramics are being replaced in clinical practice by alumina matrix composites, which are composed of alumina and zirconium. In this review, the characteristics of both materials are discussed, and the long-term results with third-generation alumina-on-alumina bearings and the associated complications are compared with those of other available ceramics. Cite this article: EFORT Open Rev 2018;3:7-14. DOI: 10.1302/2058-5241.3.170034